2006
DOI: 10.1159/000091466
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transcription Factor A (TFAM) is Increased in Rat Embryo During Placentation and Associated with Mitochondrial Differentiation

Abstract: In the current study, the mitochondrial proliferationdifferentiation process was investigated in rat embryo during the placentation process, straight after organogenesis, when there is an important oxidative metabolism activation. For this purpose, on gestational days 11, 12 and 13 we studied the mitochondrial DNA (mtDNA) content and the relative gene expression of proteins involved in mtDNA replication (mitochondrial single strand DNA binding protein (mtSSB)), mtDNA transcription (mitochondrial transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Thus, the aforementioned increase in the nuclear-encoded proteins, such as TFAM, would lead to an activation of the mtDNA transcription and all together would help the embryo mitochondria to reach a more differentiated stage through a coordinate regulation of both nuclear and mitochondrial-encoded proteins. This idea corroborates the activation of the mitochondrial differentiation process in rat embryo during the placentation period that we have previously suggested (Alcolea et al 2006). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the aforementioned increase in the nuclear-encoded proteins, such as TFAM, would lead to an activation of the mtDNA transcription and all together would help the embryo mitochondria to reach a more differentiated stage through a coordinate regulation of both nuclear and mitochondrial-encoded proteins. This idea corroborates the activation of the mitochondrial differentiation process in rat embryo during the placentation period that we have previously suggested (Alcolea et al 2006). …”
Section: Discussionsupporting
confidence: 91%
“…In middle pregnancy, rat embryo mitochondria undergo considerable morphofunctional changes (Mackler et al 1973, Shepard et al 1998, Yang et al 1998 coinciding with the switch from glycolytic to oxidative metabolism that takes place on gestational day 12 (Akazawa et al 1994, Shepard et al 1997, just when the placentary circulation is established and oxygen becomes more available to the embryo (Jollie 1986, Akazawa 2005. In addition, a previous study in our laboratory reported the activation of mitochondrial gene expression throughout the placentation period, suggesting that mitochondrial biogenesis is an active process in rat embryo during this developmental stage (Alcolea et al 2006). Therefore, embryo development during the placentation period is a suitable model to further understand the mitochondrial proliferation and differentiation processes (Justo et al 2002).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This metabolic onset entails a mitochondrial biogenic process that implies important changes in mitochondrial function, morphology, and expression, which leads to embryo mitochondria reaching a more differentiated stage (4,28,43,51).…”
mentioning
confidence: 99%
“…In this sense, diabetes-induced oxidative stress is known to cause defects in the expression, function, and structure of mitochondria (23,33,41,42), which in turn might further increase reactive oxygen species production and, thus, the diabetic complications. However, despite the fact that mitochondrial biogenesis is a critical process in embryo development (4,30,48), nothing is known about the effect of maternal diabetes on this process and about its relationship to the embryopathies associated with this pathology.…”
mentioning
confidence: 99%